Phase I clinical study of the toll-like receptor 9 agonist MGN1703 in patients with metastatic solid tumours. Issue 2 (January 2015) - Weihrauch, Martin R.; Richly, Heike; von Bergwelt-Baildon, Michael S.; Becker, Hans Jiro; Schmidt, Manuel; Hacker, Ulrich T.; Shimabukuro-Vornhagen, Alexander; Holtick, Udo; Nokay, Bahar; Schroff, Matthias; Wittig, Burghardt; Scheulen, Max E.
Abstract Purpose This study was initiated to evaluate safety, toxicity, pharmacokinetics, and pharmacodynamics of treatment with MGN1703, a novel synthetic DNA-based toll-like receptor 9 (TLR9)-immunomodulator. Methods The study consisted of an escalating single dose regimen followed by a multiple dose part. Dose levels of 0.25, 2, 10, 30, and 60 mg of MGN1703 were administered subcutaneously over 6 weeks twice weekly. Patients with at least stable disease (SD) could participate in the extension phase of the study for six further weeks. Effects on the immune status were monitored. Results 28 patients with metastatic solid tumours were included. Fatigue and activated partial thromboplastin time (aPTT) prolongation were the only two cases of drug-related grade 3 Common Terminology Criteria adverse events (CTCAE). The most frequently reported drug-related adverse events were of CTC Grade ⩽2. There was no relationship between toxicity and dose and no patient was withdrawn from the study due to drug-related AE. No drug-related serious AE (SAE) were reported. Six out of 24 patients had SD after 6 weeks of treatment and three of those remained in SD after a total of 12 weeks. Four patients were further treated in a compassionate use programme showing long-term disease stabilisation for up to 18 months. Immune assessment of cell compartments showed a non-significant increase of TLR9 expressing naïve B cells during therapy. Conclusion Twice weekly subcutaneous applications of MGN1703 in a dose of up to 60 mg are safe and well tolerated without dose-limiting toxicities. MGN1703 shows immune activation and anti-tumour efficacy in heavily pretreated patients. The recommended dose of 60 mg twice weekly is currently used in a phase II trial in small cell lung cancer and a phase III trial in colorectal cancer patients.